Reduced circulating B cells and plasma IgM levels are associated with decreased survival in sepsis - A meta-analysis - Krautz, Christian; Maier, Sarah L.; Brunner, Maximilian; Langheinrich, Melanie; Giamarellos-Bourboulis, Evangelos J.; Gogos, Charalambos; Armaganidis, Apostolos; Kunath, Frank; Grützmann, Robert; Weber, Georg (Journal of Critical Care, 2018)
BACKGROUND: B cell function and antibody production are crucial factors in host protection during inflammation. We aimed to synthesize the available evidence on the association between the reduction of circulating B cells and plasma immunoglobulin (IgM) levels and decreased survival during sepsis. METHODS: We performed a systematic search in PubMed, Embase, ISI Web of Knowledge, Cochrane Central Register of Controlled Trials, BioMed Central, and Science Direct. We selected studies with data on circulating B cells and plasma IgM levels within the initial 24 h after sepsis onset. RESULTS: In total nine studies (n = 992 patients) were identified. Circulating B cells were reduced in septic patients as compared to non-septic patients (mean difference [MD] -88.2 cells/μl; 95% confidence interval [CI] -148.6–27.9). Sepsis non-survivors showed a significant reduction of circulating B cells and IgM levels compared to sepsis survivors (MD -77.1 cells/μl; 95% CI -111.4–42.7 and MD -20.9 mg/dl; 95% CI -33.8–8.0, respectively). CONCLUSIONS: Our results suggest that a reduction of circulating B cells and IgM levels at sepsis onset are associated with decreased sepsis survival. However, due to methodological limitations and the risk of bias, we need further prospective studies to confirm this association. REGISTRATION: The protocol was registered (PROSPERO 2016:CRD42016053184).
EVALuna2:32856